High Prevalence and Genotypic Diversity of the Human Papillomavirus in Amazonian Women, Brazil. (13th August 2013) - Rocha, Danielle Albuquerque Pires; Barbosa Filho, Roberto Alexandre Alves; de Queiroz, Francisca Andrade; dos Santos, Cristina Maria Borborema
Abstract : The aim of this study was to determine the prevalence of human papillomavirus (HPV) in a women population living within the state of Amazonas, Brazil, and to determine the viral genotypes found. The study included 361 sexually active women over 18 years of age. We performed the Pap test and the molecular diagnosis for HPV DNA using polymerase chain reaction (PCR). The amplicons obtained were sequenced in automatic sequencer for genotyping. The presence of HPV DNA was found in 29.1% (105) of the women. Only 321 women presented satisfactory slides for cytological diagnosis, 97.9% (314) had normal cytology (negative for cancer), and 2.1% (7) had abnormal cytology (4 ASCUS, 1 LSIL, and 2 HSIL). The types more frequently found were HPV 16 (58.1%) and HPV 58 (20.0%). Additionally, we found more 13 types of HPV. Compared with previous studies in Brazil, our data confirmed a high prevalence and genotypic diversity of HPV in Brazilian women.